Effect of lyophilized amniotic membrane, hyaluronic acid, and their combination in preventing adhesion after tendon repair in New Zealand white rabbits (Medical Journal of Indonesia, 2014)
Background: Several promising methods to reduce the peritendinous adhesion after repair include amniotic membrane and hyaluronic acid application on the repaired tendon site. This study aimed to compare the effect of lyophilized amniotic membrane, application of hyaluronic acid, and their combination in preventing peritendinous adhesion after tendon repair in New Zealand white rabbits.Methods: 64 flexor digitorum fibularis tendon from 16 rabbits were cut and then repaired by modified Kessler technique. Samples were allocated into four test groups; group I as control had simple tendon repair, group II had amniotic membrane wrapping at repair site, group III had hyaluronic acid application at repair site, and group IV had combination of amniotic membrane wrapping and hyaluronic acid application. On 6th week, 8 tendon from each group underwent macroscopic and histologic evaluation of peritendon adhesion by Tang scoring system. The rest of samples were evaluated for tendon gliding at tenth week by measuring active and passive range of motion of metatarsophalangeal joint.Results: At 6th week, macroscopic and histologic evaluation showed that groups II, III, and IV had significantly lower peritendinous adhesion compared to control group (p < 0.05). However, there was no significant difference found among groups II, III, and IV (p > 0.05). Similar results were found in tendon gliding evaluation, groups II, III, and IV had significantly better range of motion compared to control group (p < 0.05), but there was no significant difference found between these groups (p > 0.05).Conclusion: The application of lyophilized amniotic membrane, hyaluronic acid, or their combination significantly reduce the formation of peritendinous adhesion in repaired flexor digitorum fibularis tendon in rabbit model.